IMPLEMENTASI PHPMYADMIN PADA RANCANGAN SISTEM PENGADMINISTRASIAN - Rahmawati Erma Standsyah; Intannia Sari Restu (Unisda Journal of Mathematics and Computer Science (UJMC), 2017)
A large number of letters has made and received in the administrative division, so the search data will become inefficient in terms of time and energy by using manual system. MySQL - phpMyAdmin beside of database has main advantages is the accelaration. So this research implements phpmyadmin on the design of letter administration system. The results obtained from the design of this mailing archive application can facilitate administrators in managing mail archiving.